(untitled) (Cadernos ESP, 2022)
For vaccine-preventable diseases to be controlled, eliminated or eradicated, adequate vaccination coverage is necessary. The practice aims to: present the experience of the municipality of Icapuí, Ceará, in real-time vaccination monitoring of children; improve information about vaccination coverage for children under five years of age; favoring the protection of vaccine-preventable diseases in the target public and monitoring in real time children who are eligible for vaccination and who have delayed vaccines, as well as carrying out an active search for children who have not received the vaccine. The present study is descriptive, of the experience report type, where the experience in a project promoted by the health service in the city of Icapuí, Ceará is described. It started in July 2021 with the participation of the Municipal Health Department of the municipality of Icapuí along with the Primary Care technical team with professionals from the Primary Health Care Units (UAPS).